Tourisme et lutte contre la pauvreté : opportunités et défis - Olivier Dehoorne (Études Caribéennes)
Develop tourism as a tool in the fight against poverty requires first to agree on the meaning of the word poverty and to clarify the political intentions of the project. Reflection on the reduction of poverty through the tourism can be synthesized in three steps: first, the beneficial effects of runoff from tourist revenues in host societies, then the collateral damage resulting from tourism and, finally, to define the conditions necessary to integrate positively tourism project in the host territories.In the end, it is indispensable to develop a proactive policy, because the poorest will not benefit from famous income runoff. Taking into account complex and contradictory impact of international tourism (including inflation, revenue leakage, deconstruction accelerated of local societies), it is necessary to include it in a sustained and coherent territorial project by local communities to identify real benefits.